Governo eletrônico: adoção sob a perspectiva do servidor público - Costa, Jailza Mendes da (2023)
This research aims to identify the factors that influence the adoption of digital government by public servants involved in the provision of public services in an organization in the State of Paraíba. And in this search, the multi-criteria Analytic Hierarchy Process (AHP) method was used (SAATY, 1980; GUPTA; BHASKAR; SINGH, 2017). The choice of the method is justified by the scope of the analysis that the method presents, regarding the perspective of mandatory adoption, which made it possible to fill the gap in research that analyzes the adoption of electronic government by public servants. The sample used was 31 permanent employees who work at the State Secretariat for Administration of the State of Paraíba, the majority of whom are male (63.3%), aged between 36 and 45 years, and have years of public service 10 years. The AHP Method, through the hierarchy proposed by Gupta; Bhaskar; Singh (2017), made it possible to present the weights of the main factors and sub-factors that influence the adoption of electronic government from the perspective of public servants. Among the results found, organizational factors were highlighted as the main factor motivating the adoption of electronic government by public servants, which points to the importance of support from the organization, in the sense of offering training and technical assistance to its employees and the extent to which this action may impact acceptability. And in comparison to the analysis developed by Gupta; Bhaskar; Singh (2017), the results were similar from the experts' perspective, regarding the main factors, but with different perceptions regarding the weights of some sub-factors. Which points to the perspective of how the analysis of who operates the system can be the difference in success or not in the process of implementing electronic government. Regarding the global classification of subfactors, with regard to the influence of the adoption of electronic government by public servants, the training subfactor came first, which demonstrates the importance of training these servants. And that the allocation of training resources for the organization's employees can be one of the solutions in enhancing the employee's sense of belonging, in building a digital transformation process in cooperation. It is clear that even though the insertion of ICTs in public administration is not recent, some obstacles have made it impossible to actually succeed, but it is clear that its development is in the transformation phase and government representatives need to address the issue. digital government, with the essence of public policy. The need to rethink government capacity is urgent. And the insertion of strategies, with a focus on developing the skills of employees, can be a field that will transform uncertainties, into the materialization of the digitalization of the public sector.